Simulation Calculation and Analysis of the Influence of Wake Jet on Aircraft Tail Flow Field. Issue 1 (February 2021) - Liu, Wenlin; Zhou, Pengyu; Yu, Xiongfei; Song, Zhijie; Wang, Jinku
Abstract: In order to analyze the influence of the wake jet on the tail flow field during the take-off and landing phase of the aircraft, this paper uses Computational Fluid Dynamics technology, takes an aircraft as the research object, and uses the RANS equation, Realizable k-ε turbulence model and the Delaunay unstructured meshing method. The Roe discrete scheme is used to numerically simulate the wake field of the aircraft using the coupled implicit algorithm, which is divided into two conditions: wake jet and no wake jet. The simulation results show that there is a certain back pressure zone in the wake field of the aircraft, the gauge pressure range is -272∼1067 Pa, the pressure difference at the same position in the wake field area is small, the range is -240∼60 Pa, and the wake field pressure has little correlation with the wake jet, and there is no separation vortex under the two conditions. The simulation results verify the rationality and effectiveness of the simulation calculation, and provide a certain theoretical reference for the safe take-off and landing of the aircraft.